CT and MRI of adrenal gland pathologies - Wang, Fuqin; Liu, Junwei; Zhang, Ruoxi; Bai, Yonghua; Li, Cailin; Li, Bangguo; Liu, Heng; Zhang, Tijiang (Quantitative Imaging in Medicine and Surgery, 2018)
Besides ultrasound and nuclear medicine techniques, computed tomography (CT) and magnetic resonance imaging (MRI) are commonly used to examine adrenal lesions in both symptomatic and asymptomatic patients. Some adrenal lesions have characteristic radiological features. If an adrenal nodule is discovered incidentally, determining whether the lesion is benign or malignant is of great importance. According to their biological behavior, lesions can be divided into benign (mainly: adenoma, hyperplasia, pheochromocytoma, cyst, hemorrhage, cystic lymphangioma, myelolipoma, hemangioma, ganglioneuroma, teratoma) and malignant (mainly: metastases, adrenal cortical carcinoma, neuroblastoma, lymphoma) conditions. In this paper, we review CT/MRI findings of common adrenal gland lesions.